2020
DOI: 10.1002/ab.21881
|View full text |Cite|
|
Sign up to set email alerts
|

Combining whole‐school and targeted programs for the reduction of bullying victimization: A randomized, effectiveness trial

Abstract: Despite the extensive evaluation of school‐based interventions for bullying, victimization remains a significant problem in schools. Bullying victimization is significantly predicted by contextual (school‐related) factors. As a consequence whole‐school programs have been commonly used to prevent and reduce bullying victimization. Evidence also points to individual risk factors (such as emotional distress) in predicting victimization, yet programs to prevent bullying victimization by changing these individual r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(64 citation statements)
references
References 56 publications
(114 reference statements)
1
62
0
1
Order By: Relevance
“…intervention compared to treatment as usual for SEC or offline bullying, but some evidence of a small effect for cyberbullying. As was already indicated, SEL and bullying interventions in schools tend to be lengthy and involved, and bullying interventions in particular may struggle to demonstrate effectiveness in randomized trials [ 24 ]. Since ACT Out!…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…intervention compared to treatment as usual for SEC or offline bullying, but some evidence of a small effect for cyberbullying. As was already indicated, SEL and bullying interventions in schools tend to be lengthy and involved, and bullying interventions in particular may struggle to demonstrate effectiveness in randomized trials [ 24 ]. Since ACT Out!…”
Section: Discussionmentioning
confidence: 99%
“…Even efficacious programs described as “brief” prevention curricula can last 1 week or more and involve multiple interlocking components [ 22 ]. Further, several programs that have reported favorable results in efficacy trials have not always produced the same results in effectiveness (“real world”) trials, potentially due to issues with implementation fidelity and existing, confounding antibullying programming [ 23 , 24 ]. In concluding their report from a recent effectiveness trial, Rapee et al [ 24 ] noted, “clearly, producing a sizeable impact on school-based victimization is extremely difficult.” Therefore, there is a demonstrated need for inexpensive, simple-to-implement bullying prevention programming, but achieving positive outcomes from such interventions is likely to be especially challenging.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the overall effects sizes are modest and somewhat mixed (Evans et al, 2014;Vreeman & Carroll, 2007). Although these smaller than expected effects can be partly explained by methodological issues and increased anti-bullying policy mandates by many countries, intervention studies frequently report effects were limited by insufficient school capacity to adopt and effectively implement these complex whole-school interventions , particularly in effectiveness (real-world) trials (Rapee et al, 2020;Axford et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Results from both studies showed a significant decrease in an increasing trend of bullying experience when the FSFF student curriculum was taught compared to the usual curriculum [15,19]. The two trials that did not show significant effects were a trial of a pre-primary aggression prevention program (unpublished), and a recent effectiveness trial that faced significant implementation problems [20]. Moreover, 3000 schools in Australia and some schools in Singapore, New Zealand, the USA and the UK have used/are using the Friendly Schools resources since they were first released in 2005.…”
Section: Introductionmentioning
confidence: 99%